Twinkle, twinkle, little star - Taylor, Jane, 1783-1824 (Little, Brown and Company, 2011)
"As a curious little chipmunk leaves his nest to greet the twilight, he gazes at the glittering sky above him. He can't help but also notice the sparkling dewdrops on a spider's web, the lights of the fireflies, and the shimmers of moonlight on the water. 'How I wonder what you are!' marvels the tiny creature, launching a dreamlike quest to reach for the stars."--Amazon.com.